Reduction in invasive pneumococcal disease following implementation of the conjugate vaccine in the Oxfordshire region, England. - Foster, D; Walker, A; Paul, J; Griffiths, D; Knox, K; Peto, T; Crook, D (2011)
Pneumococcal conjugate vaccine to seven capsular types has been highly effective in the US since its introduction in 2000. The same vaccine was adopted by the UK in 2006. Ongoing surveillance since 1995 of invasive pneumococcal disease (IPD) in Oxfordshire, UK, allowed assessment of the impact of vaccine intervention. The vaccine significantly reduced IPD among the target group, children under 2 years of age; incidence rate ratio (IRR)=0.62 (95 % CI 0.43-0.90) (P=0.008) comparing the 3 years pre- and post-implementation with a residual incidence of 22.4/100 000 children. The reduction was even greater when comparing 11 years pre- with the 3 years post-implementation of vaccine; IRR=0.53 (0.39-0.70) (P<0.0001). There was a marked direct effect of the vaccine evidenced by substantial reductions in the seven serotypes contained in the vaccine. There was also a clear reduction in IPD for those serotypes contained in the vaccine among those older than 2 years when comparing both the 3 and 11 year pre-PCV7 time periods, with IRR=0.57 (0.47-0.69) (P<0.0001) and IRR=0.50 (0.43-0.58) (P<0.0001), respectively, indicating a strong herd effect. There was a significant, though moderate, rise in the serotypes not contained in the vaccine, with clear evidence for replacement in some serotypes.